2015
DOI: 10.3390/cli4010001
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Self-Efficacy and Adaptation to Climate Change in Coastal Cambodia

Abstract: Abstract:In response to climate change at different spatial scales, adaptation has become one of the focal points of current research and policy developments. In the context of coastal Cambodia, there is little research on local level adaptation to climate change. Using ordinal logistic and logistic regression analyses, this study examines the relationship between perceived self-efficacy and anticipatory and reactive adaptation to climate change among 1823 households in coastal communities in Cambodia. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Several studies have shown a positive relationship between self-efficacy and willingness to address climate change [25]. Ung et al (2015) found that greater perceived self-efficacy is associated with both anticipatory and reactive adaptation to natural disasters [26]. Self-efficacy also applies to a financial management context, referring to the perceived ability to accomplish a financial goal [27].…”
Section: Financial Self-efficacymentioning
confidence: 99%
“…Several studies have shown a positive relationship between self-efficacy and willingness to address climate change [25]. Ung et al (2015) found that greater perceived self-efficacy is associated with both anticipatory and reactive adaptation to natural disasters [26]. Self-efficacy also applies to a financial management context, referring to the perceived ability to accomplish a financial goal [27].…”
Section: Financial Self-efficacymentioning
confidence: 99%
“…A great deal of evidence now shows that the capacity to mitigate or adapt depends upon a wide range of social factors such as levels of education, literacy, cohesion and equality, and upon political rights and structures . Individual adaptations or mitigations further depend upon, for example, values, knowledge, and perceived personal efficacy . Indeed, subjective perceptions of change and responsive choices may not align well with concepts of mitigation and adaptation that appear obvious to an outside observer, instead passing through ‘several layers of institutional, moral and symbolic meaning (Ref , p. 76),’ each of which may be interpreted differently by the various actors involved …”
Section: Introductionmentioning
confidence: 99%
“…Milfont [23] found that higher self-efficacy can be related to higher levels of concern, perceived risk, and environmental engagement. Previous studies have also found a positive connection between knowledge of climate change, self-efficacy, and willingness to help address climate change [23], [25]. The low perceived control expressed by participants could result in limited or no mitigation behaviors if participants do not think their behaviors have any influence on global phenomena.…”
Section: Discussionmentioning
confidence: 88%
“…Increasing participants' feelings of perceived control and self-efficacy could help foster mitigation and adaptation strategies [25]. A study of UK residents found that lack of knowledge, uncertainty or skepticism, fatalism, helplessness, and lack of enabling initiatives were all barriers preventing effective engagement with climate change [26].…”
Section: Discussionmentioning
confidence: 99%